Effect of 3-Dimensional Central Stimuli on Near Point of Convergence. (3rd July 2015) - Glimne, Susanne A.M.; Öqvist Seimyr, Gustaf; Brautaset, Rune L.
Abstract: Aim : Since an interaction between binocular disparity and the vergence system takes place in order to reduce retinal disparity, it is likely that vergence control, as measured with the near point of convergence (NPC), will be better if the target used for measurement has 3-dimensional (3-D) features in its most central parts. The aim of the present study was therefore to investigate if the NPC would give a better result using a fixation target with centrally placed 3-D features when compared with a two-dimensional (2-D) target. Methods : Twenty-three asymptomatic subjects (2 men, 21 women; average age 30.0 years ±7.36 SD) who experienced diplopia when a fixation target was brought close to the eyes had their break point NPC measured using a modified RAF-ruler. A metal cube and a printed image of the cube were used as a 3-D and 2-D stimuli. The measurements were repeated 3 times in each subject for each test condition, for a total of 6 randomized NPC measurements. Results : On average a significant difference in NPC ( p  = 0.0172) was found for break point NPC with a 3-D stimuli (mean: 7.27 cm ± 2.37 SD), giving the better result as compared with a 2-D stimuli (mean: 8.02 cm ± 2.82 SD). Comparing the most remote recorded NPC values of the 3 repeated measurements under each stimulus condition, a significant difference was found ( p  = 0.0159, t  = 2.612) with 3-D stimuli giving the better result. Conclusion : The results of this study demonstrate the influence of binocular disparity stimuli on the vergence control as NPC was better if the target used for measurement had 3-D features in its most central parts.